Women with symptoms of a urinary tract infection but a negative urine culture: PCR-based quantification of Escherichia coli suggests infection in most cases. (September 2017) - Heytens, S.; De Sutter, A.; Coorevits, L.; Cools, P.; Boelens, J.; Van Simaey, L.; Christiaens, T.; Vaneechoutte, M.; Claeys, G.
Abstract: Objectives: Our objective was to examine whether or not women with symptoms of a urinary tract infection but with a negative culture (20%–30%) do have an infection. Methods: We performed quantitative PCR (qPCR) for Escherichia coli and Staphylococcus saprophyticus, on top of a standard culture, in urine samples from 220 women with dysuria and/or frequency and/or urgency and from 86 women without symptoms. For symptomatic women, qPCR was also carried out for four sexually transmitted agents. Results: In the symptomatic group, 80.9% (178/220) of the urine cultures were positive for any uropathogen and 95.9% (211/220) were E. coli qPCR-positive. For the control group, cultures for E. coli and E. coli qPCR were positive in, respectively, 10.5% (9/86) and 11.6% (10/86). In the symptomatic group, qPCR yielded 19 positive samples for S. saprophyticus qPCR, one positive sample for Mycoplasma genitalium and one for Trichomonas vaginalis. Conclusions: These findings suggest that almost all women with typical urinary complaints and a negative culture still have an infection with E. coli .